2012
DOI: 10.1007/s00232-012-9464-0
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Endocytosed Gap Junctions by Autophagosomal and Endo-/lysosomal Pathways: A Perspective

Abstract: Gap junctions (GJs) are composed of tens to many thousands of double-membrane spanning GJ channels that cluster together to form densely packed channel arrays (termed GJ plaques) in apposing plasma membranes of neighboring cells. In addition to providing direct intercellular communication (GJIC, their hallmark function), GJs, based on their characteristic double-membrane-spanning configuration, likely also significantly contribute to physical cell-to-cell adhesion. Clearly, modulation (up-/down-regulation) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 84 publications
1
35
0
Order By: Relevance
“…Thirdly, in addition to gap junctions mediating intercellular communication, they have been proposed to play a role in cell-cell adhesion (Elias et al, 2007;Falk et al, 2012), which might impact upon processes such as wound healing. For example, in wounded skin, up-regulation of Cx30 and Cx26 in all epidermal keratinocyte layers, and a concomitant decrease in Cx43 at the wound edge, are proposed to co-ordinate the keratinocyte wound healing response (Coutinho et al, 2003;Churko and Laird, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, in addition to gap junctions mediating intercellular communication, they have been proposed to play a role in cell-cell adhesion (Elias et al, 2007;Falk et al, 2012), which might impact upon processes such as wound healing. For example, in wounded skin, up-regulation of Cx30 and Cx26 in all epidermal keratinocyte layers, and a concomitant decrease in Cx43 at the wound edge, are proposed to co-ordinate the keratinocyte wound healing response (Coutinho et al, 2003;Churko and Laird, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In a complex process, internalization of GJ occurs in form of a peculiar double membrane structure called annular gap junction (AGJ) which are constitutively degraded via autophagy. 54,55 Autophagy proteins associated with autophagosome formation and maturation, ATG5 and LC3, has been shown to be localized to AGJ 56 and the autophagy receptor p62 has been found to be co-localized with connexin isotypes, Cx50 and Cx43. 57 Following traumatic brain injury (TBI), autophagy inhibition caused increased levels of phosphorylated connexin 43 (pCx43) in hippocampal astrocytes, indicating autophagy based degradation of GJs.…”
Section: Autophagy Regulation Of Gap Junctionmentioning
confidence: 99%
“…In the early endosomes, the ubiquitin binding proteins Hrs (hepatocyte growth factor-regulated tyrosine kinase substrate) and Tsg101 (tumor susceptibility gene product 101) interacts with ubiquitinated connexins and determines whether the connexins are targeted for recycling or for deubiquitination followed by degradation (Leithe et al, 2009). Connexins targeted for destruction may follow several alternative endocytotic pathways, however, there is increasing evidence suggesting that the final destination is lysosomal degradation (Laing et al, 1997; Musil et al, 2000; Girao and Pereira, 2003; Rivedal and Leithe, 2005; Piehl et al, 2007; Falk et al, 2012). …”
Section: Ubiquitinationmentioning
confidence: 99%
“…The role of the proteasomes in endocytosis and degradation of connexins from gap junctional plaques is not clear. Several studies have demonstrated that endocytosis of Cx43 is repressed in the presence of proteasomal inhibitors, suggesting that there may be an intricate interplay between lysosomes and proteasomes as reviewed in (Kjenseth et al, 2010; Falk et al, 2012). …”
Section: Ubiquitinationmentioning
confidence: 99%